Innovating medical education using a cost effective and scalable VR platform with AI-Driven haptics - Abhishek Kumar; Abdul Khader Jilani Saudagar; Ankit Kumar; Yazeed Masaud Alkhrijah; Linesh Raja (Scientific Reports)
Abstract Virtual Reality (VR) technology offers a scalable and cost-effective approach to overcome the challenges of traditional medical training, including high expenses, limited resources, and ethical issues. This study presents a VR-based medical training platform that combines high-fidelity 3D models, real-time haptic feedback, and AI-driven adaptive learning to deliver interactive and immersive instructions for a wide range of medical procedures, from basic tasks to complex surgeries. In a randomized controlled trial, participants trained with the VR platform demonstrated significant gains over those using conventional methods, with a 42% improvement in procedural accuracy, a 38% reduction in training time, and better skill retention. The VR system also led to a 45% decrease in error rates and a 48% increase in trainee confidence. These findings highlight the platform’s capacity to personalize training according to individual performance, resulting in superior learning outcomes and enhanced procedural skills. By providing consistent, standardized, and immersive learning experiences, the platform effectively bridges the gap between theory and practice, representing an innovative and scalable advancement in medical education.